The dynamic emergence of GATA1 complexes identified in in vitro embryonic stem cell differentiation and in vivo mouse fetal liver - Xiao Yu; Andrea Martella; Petros Kolovos; Mary Stevens; Ralph Stadhouders; Frank G. Grosveld; Charlotte Andrieu-Soler (Haematologica, 2020)
GATA1 is an essential transcriptional regulator of myeloid hematopoietic differentiation towards red blood cells. During erythroid differentiation, GATA1 forms different complexes with other transcription factors such as LDB1, TAL1, E2A and LMO2 (“the LDB1 complex”) or with FOG1. The functions of GATA1 complexes have been studied extensively in definitive erythroid differentiation; however, the temporal and spatial formation of these complexes during erythroid development is unknown. We applied proximity ligation assay (PLA) to detect, localize and quantify individual interactions during embryonic stem cell differentiation and in mouse fetal liver (FL) tissue. We show that GATA1/LDB1 interactions appear before the proerythroblast stage and increase in a subset of the CD71+/TER119− cells to activate the terminal erythroid differentiation program in 12.5 day FL. Using Ldb1 and Gata1 knockdown FL cells, we studied the functional contribution of the GATA1/LDB1 complex during differentiation. This shows that the active LDB1 complex appears quite late at the proerythroblast stage of differentiation and confirms the power of PLA in studying the dynamic interaction of proteins in cell differentiation at the single cell level. We provide dynamic insight into the temporal and spatial formation of the GATA1 and LDB1 transcription factor complexes during hematopoietic development and differentiation.